Implementasi Manajemen Pembelajaran Daring Pada Masa Pandemi Covid-19 - Dina W. Anugraheni; Setyo Budi Utomo; Stefanus M. Lahade; Sophia Trisatyawati; Yari Dwikurnaningsih (Journal Prakarsa Paedagogia, 2021)
The implementation of the transition from face-to-face learning to online learning requires the preparedness of all educators and students so that the educational goals that have been set can be realized. This study aims to provide a description related to the implementation of online learning at the Satya Wacana Christian High School Salatiga City, along with the difficulties encountered and endeavours to solve them. This research was conducted through a qualitative descriptive approach, with the determination of research subjects through purposive sampling. Data retrieval in the study was carried out by interviewing and documentation studies at the Satya Wacana Christian High School Salatiga. The results of the study found several problems from the implementation of online learning at the Satya Wacana Christian High School Salatiga, such as impediments in managing online learning. Several solutions are then described by the researcher as an effort to solve the issues discovered.